Antibiotic potentiating effect of Bauhinia purpurea L. against multidrug resistant Staphylococcus aureus - Limboo, Kundhey Hang; Singh, Bimala (Frontiers in Microbiology, 2024)
Bauhinia purpurea L. is a medium-sized tree from the family Fabaceae. The plant is traditionally used as medicine by different tribes in Sikkim. The present study aimed to evaluate the modulation in minimum inhibitory concentration (MIC) of the bark methanol extract of Bauhinia purpurea L. against the clinical isolates of multidrug resistant Staphylococcus aureus. The synergistic activity of the test plant extract with different classes of antibiotics was also evaluated. The methanol extract of Bauhinia purpurea exhibited modulation by a 16-fold reduction in the MIC of clindamycin against both resistant and susceptible isolates, followed by penicillin and gentamicin, whereas a maximum of only a 4fold MIC reduction was observed with ciprofloxacin. The lowest minimum inhibitory concentration and minimum bactericidal concentration showed by the plant extract was 0.48 mg/mL and 0.97 mg/mL, respectively. The methanol extract of Bauhinia purpurea exhibited synergistic activity with penicillin, gentamicin, ciprofloxacin, and clindamycin against most of the tested isolates of multidrug-resistant Staphylococcus aureus (MDR-SA). Gas chromatography-mass spectrometry analysis of Bauhinia purpurea L. bark methanol extract revealed 16 phytocompounds. The results provide an insight into the potential antibacterial property of the plant extract in terms of its antibiotic MIC modulation and synergistic properties with the selected antibiotics. This is the first report of the antibiotic potentiation property of Bauhinia purpurea L., collected from Sikkim, India.